Post-traumatic Growth in Breast Cancer Patients: A Qualitative Phenomenological Study - Rahele Fallah; Fatemeh Keshmir; Farah Lotfi Kashani; Eznollah Azargashb; Mohammad Esmaeel Akbari (Middle East Journal of Cancer, 2012)
Background: Studies about cancer-related trauma have shown that psychological reactions to the disease are not exclusively negative but most patients also report positive experiences. These positive perceptions are also called post-traumatic growth and benefit patients psychologically, spiritually, and physically. Therefore,we have conducted a study about how women with breast cancer perceive posttraumatic growth and the recognition of its dimensions in Iran.Methods: This qualitative study was conducted by using Interpretative Phenomenological Analysis. A total of 23 women with breast cancer who met the inclusion criteria were selected after which patients completed a researcher-generated open-ended questionnaire. Data were analyzed according to the guidelines for the Interpretative Phenomenological Analysis and Smith method.Results: Participants’ perceptions in this study about post-traumatic growth included three themes: spiritual growth, appreciation of life, and increased personal strengths.Conclusion: Themes found in this study conformed to dimensions according to the Tedeschi and Calhoun theory of post-traumatic growth. However, relations with others were not found in the present study. We propose that interventions should be designed and implemented in order to facilitate and enhance post-traumatic growth.